Pertuzumab, trastuzumab, and docetaxel for HER2-positive metastatic breast cancer (CLEOPATRA study): overall survival results from a randomised, double-blind, placebo-controlled, phase 3 study - Swain, Sandra M.; Kim, Sung-Bae; Cortés, Javier; Ro, Jungsil; Semiglazov, Vladimir; Campone, Mario; Ciruelos, Eva; Ferrero, Jean-Marc; Schneeweiss, Andreas; Knott, Adam; Clark, Emma; Ross, Graham; et al. (The lancet. Oncology, 2013)
Background - CLEOPATRA is a phase 3 study to compare the efficacy and safety of pertuzumab, trastuzumab, and docetaxel with placebo, trastuzumab, and docetaxel in patients with HER2-positive first-line metastatic breast cancer. The results of the primary analysis showed significantly longer median progression-free survival in the pertuzumab group than in the placebo group. Interim analysis of overall survival favoured the pertuzumab group but was not significant. Here, we report results for overall survival after an additional year of follow-up. - Methods - The study was a double-blind randomised trial undertaken at 204 centres in 25 countries. Patients with HER2-positive metastatic breast cancer who had not received previous chemotherapy or biological treatment for their metastatic disease were randomly assigned to receive either pertuzumab, trastuzumab, and docetaxel (n=402) or the same regimen with a matching placebo replacing pertuzumab (n=406). Randomisation was in a 1:1 ratio, stratified by geographical region and previous treatment status. The primary endpoint was progression-free survival (assessed independently), which has been reported previously; no follow-up data were gathered for the primary endpoint. Secondary endpoints included overall survival, progression-free survival (assessed by investigator), objective response rate, and safety. Median follow-up was 30 months in both groups. Efficacy endpoints were analysed in the intention-to-treat population and safety was analysed by treatment received. The study is completed but safety and survival data continue to be followed up. This trial is registered with ClinicalTrials.gov, number NCT00567190. - Findings - In the intention-to-treat population, 267 patients died by data cutoff (May 14, 2012), 154 (38%) of 406 in the placebo group and 113 (28%) of 402 in the pertuzumab group. Median overall survival was 37·6 months (95% CI 34·3-NE [not estimable]) in the placebo group but had not been reached (95% CI 42·4-NE) in the pertuzumab group (hazard ratio 0·66, 95% CI 0·52-0·84; p=0·0008). Investigator-assessed median progression-free survival was 12·4 months (95% CI 10·4-13·5) in the placebo group and 18·7 months (16·6-21·6) in the pertuzumab group (hazard ratio 0·69, 95% CI 0·58-0·81). Serious adverse events were reported in 115 (29%) of 396 patients who received placebo, trastuzumab, and docetaxel and 148 (36%) of 408 who received pertuzumab, trastuzumab, and docetaxel, and included febrile neutropenia, neutropenia, diarrhoea, pneumonia, and cellulitis. Overall, adverse events were similar to those reported at the primary analysis with respect to frequency, severity, and specificity. - Interpretation - Our analysis shows a significant improvement in overall survival with pertuzumab, trastuzumab, and docetaxel in patients with HER2-positive metastatic breast cancer, compared with placebo, trastuzumab, and docetaxel. Since this effect was not achieved at the expense of adverse events, this regimen represents a substantial improvement on the standard of care for this population of patients.